Udaka To Precision Hydration: An Ayurvedic Policy Framework for Personalized Water Management in Twenty-First Century Healthcare - Dr Hrutvij Kishor Kharate; Dr. Shelar Suvarna; Dr. Rokade Bharat; Dr. Jayshri Namdeo Tayade; Dr. Umesh Tekawade; Dr. Akanksha Dasila (The Bioscan, 2026)
Background- Ayurveda, through the concept of Udaka, presents an individualized framework for waterregulation that has not yet been systematically examined within the context of precision medicine orhealthcare policy. The Ayurvedic concept of Udaka provides a multidimensional framework forindividualized hydration that complements modern physiology and may inform future precisionhealthcare and evidence-informed hydration policy. Despite remarkable advances in hydration science,current recommendations remain predominantly population-based and often fail to account forsubstantial inter-individual variability arising from age, physiology, climate, disease, occupation, andlifestyle.Objectives - To critically review the concept of Udaka and evaluate its relevance to contemporaryhydration science, precision medicine, and healthcare policy. Evaluate current hydrationrecommendations and their limitations. Explore the role of individualized hydration in precisionhealthcare.Methods: A comprehensive narrative review was conducted with the use of biomedical databases,international policy documents, and classical Ayurvedic texts. Scientific literature on precision medicine,health-climate interactions, and preventive healthcare was critically reviewed together with primaryAyurvedic literature.Results: In particular, the review revealed considerable conceptual convergence between the currentscientific concepts regarding hydration and the concept of Udaka in Ayurveda. The current scientificliterature confirms the understanding of hydration as a dynamic process that involves variousmechanisms of neuroendocrine regulation, renal control, metabolism, environment and behaviour. At thesame time, Ayurveda views Udaka as a systemic parameter that affects physiological homeostasis and isassociated with the processes of nourishment, hydration, circulation, temperature control and excretion.Both frameworks accept the idea of differentiating hydration needs depending on an individual andexternal conditions. Nonetheless, existing public health policies mostly concentrate on issues of universalwater access, water quality and sanitation, without paying much attention to the problem of assessmentof individual hydration needs. On the basis of the findings, the Udaka-Based Precision HydrationConceptual Framework was elaborated.Conclusion: The concept of Udaka reveals an innovative interdisciplinary angle to rethink the issue ofhydration in the light of personalized approach rather than generic recommendations concerning fluidintake. The potential of integration of Ayurveda with modern hydration science can help to develop theprecision hydration strategies that would contribute to the development of preventive medicine,increase climate resilience, and be used in future policy making on the issue.